TO THE QUESTION ESPECIALLY OF MODERN MILITARY THREATS RUSSIA IN THE CONTEXT OF GEOPOLITICAL CONFRONTATION INCREASING IN SOUTH STRATEGIC DIRECTIONS - David Sergeyevich Fedotov (Современная наука и инновации)
The influence of the latest security threats identifies factors, which may cause aggravation and create security risks of the Russian Federation. Identify indicators for the military-technological defense security. Criterions for safety in the increasing geopolitical confrontation context are established.